Quality services for academic staff in universities - Ali, Asem Shehadeh Saleh (Global Business Leaders, 2011)
This paper is trying to present a framework for the academic staff that can be used to develop a quality-based system for development and management within the context of an educational cum training organization. The paper presents the structure and components of such systems that utilizes total quality management (TQM) concepts, and discuss the opportunities afforded by introducing quality concepts into academic development and the problems and pitfalls involved in undertaking such an endeavor. Keywords : Quality - definition – demands-universities – TQM - TQS - development